Degrowth and the Global South? How institutionalism can complement a timely discourse on ecologically sustainable development in an unequal world - Claudius Gräbner-Radkowitsch; Birte Strunk (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2022)
The goal of this paper is twofold: first, it assesses the current state of collaboration between institutionalist economics and the academic degrowth discourse on the topic of global inequalities. Since a systematic literature review of the current degrowth discourse shows that the level of such collaboration is limited, the second goal of the paper is to outline avenues through which institutionalist scholars could contribute to the current academic degrowth discourse. These include the provision of theories of institutional change, a methodological reflection of selected formal models, and substantive insights on the co-evolution of institutions and technological change.
Keywords: B52; O44; Q01; Q57; 330; degrowth; institutions; development; core-periphery relations; structuralism; dependency; planetary boundaries